Recommended dietary allowances - National Research Council (U.S.). Subcommittee on the Tenth Edition of the RDAs.; National Institutes of Health (U.S.); National Research Council (U.S.). Committee on Dietary Allowances (Washington, D.C. : National Academy Press, 1989)
Defnition and Applications -- Energy -- Carbohydrates and Fiber -- Lipids -- Protein and Amino Acids -- Fat-Soluble Vitamins -- Water-Soluble Vitamins -- Minerals -- Trace Elements -- Water and Electrolytes -- Other Substances in Food.
Summary -- Defnition and Applications -- Energy -- Carbohydrates and Fiber -- Lipids -- Protein and Amino Acids -- Fat-Soluble Vitamins -- Water-Soluble Vitamins -- Minerals -- Trace Elements -- Water and Electrolytes -- Other Substances in Food.
Revised edition of: Recommended dietary allowances / Committee on Dietary Allowances, Food and Nutrition Board, Division of Biological Sciences, Assembly of Life Sciences, National Research Council. 9th rev. ed. 1980.
Supported by funds from the National Institutes of Health, United States Public Health Service, contract no. NO1-DK-8-2236.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Nutrition; Diet; Nutrition policy; Diet in disease; Ingestion; Nutrition Policy; Nutritional Physiological Phenomena; Diet; Nutrition; Alimentation; Régimes alimentaires; Politique alimentaire; diet; HEALTH & FITNESS -- Nutrition; HEALTH & FITNESS -- Diets; MEDICAL -- Nutrition; MEDICAL -- Nursing -- Nutrition; HEALTH & FITNESS -- Food Content Guides; Nutrition policy; Ingestion; Diet in disease; Diet; Nutrition; Levensmiddelen; Toevoegingen; Nutrition; Diet; United States; Standards; Overseas item; consumptiepatronen; consumption patterns; voedsel; food; voedselsamenstelling; food composition; food hygiene; voedingsmiddelen; foods; voedingsfysiologie; nutrition physiology; voedingstoestand; nutritional state; voedingswaarde; nutritive value; eigenschappen; properties; kwaliteit; quality; Nutrients; Voedingsstoffen